FAKTOR PENDIDIKAN, PENGETAHUAN, PARITAS, DUKUNGAN KELUARGA DAN PENGHASILAN KELUARGA YANG BERHUBUNGAN DENGAN PEMANFAATAN PELAYANAN ANTENATAL - Gita Nirmala Sari Nirmala Sari; Shentya Fitriana; Diana Hartaty Anggraini (Jurnal Ilmu dan Teknologi Kesehatan, 2015)
Antenatal care is an important way to monitor and support the health of pregnant womenandcan give birth to a healthybaby through normal delivery. Antenatal care consists ofseveral series of visits of pregnant women known as K1 and K4 indicators. The utilizationof antenatal care by a pregnant woman can be seen from the coverage of antenatal care,monitored via the service of the first (K1) until the fourth visit(K4)of antenatal care forpregnant women. The purpose of this study is to determine the factors (education, knowledge,parity, family income and social support) related to the utilization of antenatal care at thePrimary Health Center in the area of East Jakarta in 2014. This study used an analyticalmethod with Cross Sectional Survey (cross-sectional). The Datawere prospectively gatheredfrom interviews and questionnaires conducted at the same time based on the exclusion andinclusion criteria from October to November 2014, The analysis result using the Chi-squaretest showed a significant correlation between education (p=0,0038), knowledge (p=0,001),parity (p=0,005), family income (p=0,02), and social support (p=0,017) with the utilizationof antenatal care (p <0.05) and the result of the multiple regression multivariate analysisfound that the mostdominant factor related to the utilization of antenatal care was knowledge(p=0,007).